Introducing the Letters of Qalqalah in Tajweed using Card Sort in Qur'an Learning - Shahbal, Ammar Ali; Nurrohim, Ahmad (Universitas Muhammadiyah Surakarta, 2023)
Hijaiyah letters are the basic knowledge capital for reading the Quran because it is the basis of the formation of verses in the Qur'an. If a person already knows the hijaiyah letters, he will find it easier to learn to the next stage in learning to read the Quran. This research was motivated by the learning conditions of the Qur'an which showed that the ability to cooperate, activeness and learning outcomes of students was still relatively low. Teachers still use conventional learning models, so learning is dominated by teachers. The dominance of teachers in this learning process makes students passive-minded so that they more often wait for what the teacher will give them than find for themselves the knowledge, skills and attitudes they need. In this case, researchers try to overcome these problems through the application of card sort learning methods. The application of these learning methods is expected to help students' understanding in the subjects of the Qur'an so that the ability to cooperate, activeness and learning outcomes of students can increase. The type of research used in this study is Classroom Action Research (PTK) which consists of two cycles, the first cycle two meetings, the second cycle one meeting. The target of the study is learners. The process of implementing classroom actions includes: (1) the planning stage, researchers prepare plans from each cycle including Learning Implementation Plans (RPP), methods, media, and materials. (2) the implementation stage, the researcher applies the card sort learning method to learning the subject matter of the law of qalqalah reading (3) the observation stage, making observations related to the researcher's activities and also the response to the condition of students according to the observation sheet that has been previously provided and (4) the reflection stage.